Assessment of employee engagement at NTTPS LTD –a case study in HRM practices - Srilakshmi, B.; Dadhabai, Dr. Sundari (International Journal of Engineering and Technology, 2018)
The purpose of this study was to investigate the relationship between human resource (HR) practices, employee engage-ment and organizational citizenship behaviors (OCB) in selected firms. This study contributes to our understanding of the mediating and moderating processes through which human resource management practices are linked with behavioral outcomes. We developed and tested a moderated mediation model linking perceived human resource management prac-tices to organizational citizenship behavior and turnover intentions. Drawing on social exchange theory, our model posits that the effect of perceived human resource management practices on both outcome variables is mediated by levels of employee engagement, while the relationship between employee engagement and both outcome variables is moderated by perceived organizational support and leader-member exchange. Overall, data from some employees in a service sector organization support this model. This suggests that the enactment of positive behavioral outcomes, as a consequence of engagement, largely depends on the wider organizational climate and employees’ relationship with their line manager. Im-plications for practice and directions for future research are discussed.